A Q factor analysis of college undergraduate students’ study behaviors - Yang, Yang; Bliss, Leonard B. (My University, 2015)
This study attempted to better understand the study behaviors of undergraduate students by categorizing students into distinctive typologies based on their self-reported study behaviors through an exploratory approach -- Q factor analysis. A sample of 152 undergraduate students completed a survey instrument, the Study Behavior Inventory. The Q factor analysis yielded a two-factor structure. Participants exhibiting the first behavioral type demonstrated reflective, well-organized study behaviors and favored high-level thinking; thus were described as “Organized Holistic Learners”. Those exhibiting the second behavioral type were found to manage time poorly and primarily focus on memorizing facts; thus were labeled “Disorganized Procrastinators”. Type 1 students had significantly higher average GPAs than Type 2 students. Student type was a significant predictor of academic achievement, as measured by self-reported GPA above and beyond students’ attribute variables including sex, age, major, and enrollment status. Theoretical and practical implications were discussed.